Metal sensitivity in patients with orthopaedic implants: a prospective study - Frigerio, Elena; Pigatto, Paolo D.; Guzzi, Gianpaolo; Altomare, Gianfranco (Contact dermatitis, 2011)
Background. Sensitization to orthopaedic implant materials is an unpredictable event that might affect implant performance. Objectives. In candidates for hip or knee joint prosthesis implantation, to evaluate preoperative assessments for identifying patients with metal sensitivity, to determine the percentage of patients who developed metal sensitivity at 1 year after prosthesis implantation, and to examine the clinical relevance of patch tests and lymphocyte transformation tests (LTT‐MELISA®) for the evaluation of metal sensitization. Patients and methods. A total of 100 patients referred for total hip or total knee arthroplasty were assessed preoperatively and then at 1 year post‐implantation by means of patch tests with the metals present in the implant alloys. In a pilot study, 20 patients also underwent both patch testing and a lymphocyte transformation test (LTT‐MELISA®) for the same metals. Results. Only 72 of 100 patients were patch tested both before and after surgery, and 12 of 20 also underwent LTT‐MELISA® before and after surgery. Of 31/100 patients with an apparent history of nickel sensitivity determined during preoperative assessment of subjects, 12 tested negative on both tests, and 4 with a negative history of nickel sensitivity tested positive. One year post‐implantation (72 patients), 5 patients who had initially tested negative for a metal allergy became positive for at least one or more metal constituents of the prosthesis on at least one or the other test. Conclusions. Given the discrepancies between the information obtained while taking patient histories and test results, preoperative history‐taking alone appears to be insufficient for identifying patients with metal sensitivity. Moreover, the increase in the percentage of patients who tested positive for metal sensitivity 1 year post‐implantation suggests the possibility of prosthesis‐induced sensitization. Therefore, objective determination of metal sensitivity at preoperative assessment should be considered in planning arthroplasty intervention, as it would help the surgeon in selecting the most appropriate prosthesis for the patient and could benefit implant performance.